Optional Protocol on the Involvement of Children in Armed Conflict - Garayová, Lilla (International Children's Rights, 2024)
The Optional Protocol to the Convention on the Rights of the Child on the involvement of children in armed conflict is a legal instrument aimed at prohibiting the recruitment and use of children in armed hostilities. This chapter provides a historical and legal analysis of the Protocol, exploring its evolution, core provisions, and implementation challenges. The discussion begins by contextualizing the Protocol within two primary international legal frameworks: international humanitarian law and international human rights law. These frameworks, including the Geneva Conventions, the Convention on the Rights of the Child (CRC), and the Rome Statute, establish the minimum standards for protecting children in armed conflicts. Specific attention is given to the Protocol’s Articles 1-13, which address the prohibition of child recruitment by both state and non-state entities, establish the minimum age for voluntary and compulsory recruitment, and mandate the demobilization and rehabilitation of former child soldiers. The chapter critically examines the Protocol’s limitations, including its non-absolute language and its focus on “direct” rather than “indirect” participation in hostilities, which could allow for the indirect involvement of children in conflict-related activities. The analysis also underscores the essential role of the Committee on the Rights of the Child and civil society in ensuring compliance with the Protocol’s standards and promoting its universal ratification. Despite these achievements, ongoing armed conflicts highlight the persistent challenges in safeguarding children’s rights, necessitating an intensified commitment to enforcing and strengthening international legal standards.Keywords: Optional Protocol, child soldiers, armed conflict, international humanitarian law, children’s rights, CRC, non-state armed groups, demobilization, international human rights law